Short Communication: Proximate analysis, amino acid profile and albumin concentration of various weights of Giant Snakehead (Channa micropeltes) from Kapuas Hulu, West Kalimantan, Indonesia (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Pratama WW, Nursyam H, Hariati AM, Islamy RA, Hasan V. 2020. Short Communication: Proximate analysis, amino acid profile and albumin concentration of various weights of Giant Snakehead (Channa micropeltes) from Kapuas Hulu, West Kalimantan, Indonesia. Biodiversitas 21: 1196-1200. Fish is an important foodstuff due to its nutritional value and high protein. One of popular fish as a foodstuff in tropical Asia is giant snakehead fish (Channa micropeltes). This study aims to examine the proximate composition, amino acid profile, and albumin concentration of giant snakeheads in various weights and to determine the best weight of giant snakeheads according to the proximate, amino acid, and albumin concentration. This research used natural-caught giant snakehead as a material of study, which was categorized into 4 weight sizes consisting of 4-5 grams (B1), 6-14 grams (B2), 15-34 grams (B3), 35-300 grams (B4). Based on the results of the test, the highest water content was found in B1 of 80.5%, the highest levels of protein and fat were in the B4 group of 16.8% and 1.7%, respectively. The highest total amino acid profile was found in B4, with the highest composition of essential amino acids, lysine, which was 2.02%, while the composition of the highest non-essential amino acid in glutamate was 3.60%. The highest albumin levels were in the B4 group which was 16.7%. According to the result of this research, the best weight to consume according to the proximate analysis (Protein, fat content), amino acid profile, and albumin concentration is a giant snakehead at the weightiest of 35-300 grams (B4).
Keywords: Albumin level, amino acid, Channa micropeltes, Kapuas Hulu, West Kalimantan